2012
DOI: 10.1007/s13142-012-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful dissemination of Fun 5 — a physical activity and nutrition program for children

Abstract: Examine the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) of an evidence-based physical activity and nutrition curriculum disseminated to after-school programs. Program components included nutrition, physical activity, and sustainability, adapted to after-school settings and disseminated across 4years (2004)(2005)(2006)(2007)(2008). The RE-AIM framework was used to evaluate dissemination quality through direct observations, surveys, and interviews. In the final year, the Fun 5 progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
3
34
1
Order By: Relevance
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).Several studies have focused on the sustainability of coalitions aimed at implementing EBIs, including the Communities That Care (CTC) coalition-based prevention system (51) and the PROSPER community-university partnership model (56). A study of 110 CTC sites in Pennsylvania found that 90% of coalitions continued after the three-year initial funding period, with 3-8% of sites terminating each year after (36).…”
supporting
confidence: 86%
“…For school-based programs, inadequate staffing and administrative support hindered sustainment. This finding is consistent with recent studies that suggest that administrative support, consistent resources, and staff stability and buy-in are particularly important in the school context (70,84,90,146).Several studies have focused on the sustainability of coalitions aimed at implementing EBIs, including the Communities That Care (CTC) coalition-based prevention system (51) and the PROSPER community-university partnership model (56). A study of 110 CTC sites in Pennsylvania found that 90% of coalitions continued after the three-year initial funding period, with 3-8% of sites terminating each year after (36).…”
supporting
confidence: 86%
“…[1] Frankly, this comment has no relevance to the reported Fun 5 program. As we reported previously, the program only costs $1/ month/child [2]-which includes the cost of a comprehensive evaluation (removing the comprehensive evaluation would decrease costs by about 1/3). Further, the enthusiasm of the group leaders implementing Fun 5, as evidenced in the reported process evaluation, sustainability, and organizational results are overwhelmingly positive, especially as the program reached maturity in the later years [2].…”
mentioning
confidence: 77%
“…As we reported previously, the program only costs $1/ month/child [2]-which includes the cost of a comprehensive evaluation (removing the comprehensive evaluation would decrease costs by about 1/3). Further, the enthusiasm of the group leaders implementing Fun 5, as evidenced in the reported process evaluation, sustainability, and organizational results are overwhelmingly positive, especially as the program reached maturity in the later years [2]. Now to the bigger picture-our paper was sharing the lessons learned from a successful dissemination, which we believe can be successful in similar contexts and among similar child groups.…”
mentioning
confidence: 77%
See 2 more Smart Citations